(untitled) (Web of Teachers: Inderscience Research, 2025)
Animal world state cadastre — natural resources, animals the world and his/her various kind types control to do, to protect to do and manage This is a system. of the system effective activity to conduct for modern technologies , especially artificial from the capabilities of intelligence (SI) use important importance has.Artificial intellect and car study methods application animal of the world various aspects further effective observation , data analysis to do and results based on decisions acceptance to do opportunity SI technologies , for example , animal migration directions , there to live of places change identification , animal population dynamics analysis in doing usage possible . Of these all-ecological balance conservation, species disappeared to leave road not to put and legal control strengthening such as tasks solution in doing help gives. This annotation, animal world state cadastre effective in the conduct artificial intellect role and his/her opportunities about briefly information This gives methods using many thin ecological issues in solution artificial from the intellect use, future animal of the world provides improved monitoring and his/her stability to increase service does.